Acute bacterial meningitis. Issue 3 (June 2021) - Wall, Emma C.; Chan, Jia Mun; Gil, Eliza; Heyderman, Robert S.
Abstract : Purpose of review: Community-acquired bacterial meningitis is a continually changing disease. This review summarises both dynamic epidemiology and emerging data on pathogenesis. Updated clinical guidelines are discussed, new agents undergoing clinical trials intended to reduce secondary brain damage are presented. Recent findings: Conjugate vaccines are effective against serotype/serogroup-specific meningitis but vaccine escape variants are rising in prevalence. Meningitis occurs when bacteria evade mucosal and circulating immune responses and invade the brain: directly, or across the blood–brain barrier. Tissue damage is caused when host genetic susceptibility is exploited by bacterial virulence. The classical clinical triad of fever, neck stiffness and headache has poor diagnostic sensitivity, all guidelines reflect the necessity for a low index of suspicion and early Lumbar puncture. Unnecessary cranial imaging causes diagnostic delays. cerebrospinal fluid (CSF) culture and PCR are diagnostic, direct next-generation sequencing of CSF may revolutionise diagnostics. Administration of early antibiotics is essential to improve survival. Dexamethasone partially mitigates central nervous system inflammation in high-income settings. New agents in clinical trials include C5 inhibitors and daptomycin, data are expected in 2025. Summary: Clinicians must remain vigilant for bacterial meningitis. Constantly changing epidemiology and emerging pathogenesis data are increasing the understanding of meningitis. Prospects for better treatments are forthcoming.